Prevalence of Bacterial Vaginosis among the PID Patients in Bangladesh (Faridpur Medical College Journal, 2011)
A cross sectional study was conducted on patients attending at the outpatient department of Gynaecology and Obstetrics of Dhaka Medical College Hospital, Dhaka during the period of July, 2007 to December, 2007. Two hundred sexually active female in the age group of 15-45 years, with vaginal discharge and itching, were selected for the study. Among them 143 having only vaginal discharge and itching without PID (Pelvic inflammatory disease) and 57 patients having vaginal discharge and itching with PID. A detailed history and a thorough clinical examination of all the cases were done. After making the clinical diagnosis of BV (Bacterial vaginosis) by Amsels criteria, diagnosis also carried out with Acridine orange staining, Gram stain Nugent criteria. Out of 200 women, 48 (24%) cases were diagnosed as having bacterial vaginosis by applying Amsel's clinical criteria. The rate of detection of bacterial vaginosis was 23% by Gram stain Nugent criteria and 24.5% by acridine orange staining. In this study BV was diagnosed in 31(54.39) cases among the PID patients and 17(11.89) among the women having only vaginal discharge and itching. This study shows the increased association of BV in PID patients of Bangladesh. Key words: Bacterial vaginosis; Sexually Transmitted Diseases DOI: 10.3329/fmcj.v6i1.7403 Faridpur Med. Coll. J. 2011;6(1): 10-13